PEMASARAN BAWANG MERAH DI DESA TONSEWER SELATAN KECAMATAN TOMPASO BARAT - Lasmaria Elisabet Marbun; Juliana R. Mandei; Ribka M. Kumaat (AGRI-SOSIOEKONOMI, 2018)
This study aims to analyze marketing channels and the efficiency of onion marketing in South Tonsewer Village, west Tompaso District. The data used are primary data and secondary data. Primary data is obtained through a list of questions that have been prepared while secondary data obtained from BP3K Office District West Tompaso, BPS (Central Statistics Agency), Internet and previous research on Marketing. Farmer samples were collected using Simple Random Sampling method and for marketing institution using snowball sampling method. The number of samples of farmers is 25 people. The data are presented in tabular form and then analyzed descriptively. The concept of measurement of variables used is the selling price, the number of onion and marketing costs. The results showed that marketing channels in Tonsewer Selatan Village, Tompaso Barat District consisted of 4 (1) farmers - Kawangkoan market retailers - consumers, (2) farmers - seller retailers Langowan market - consumers, (3) farmers - collectors village - Tomohon market-consumer merchants, and (4) farmers - village wholesalers - wholesalers of Bitung port - consumers. Based on the value of price transmission elasticity, marketing margin, farmer's share, and profit-to-cost ratio indicate that four marketing channels are not efficient. an efficient marketing channel based on the value of price transmission elasticity, marketing margins, and farmer's share, two efficient marketing channels based on farmer's share and cost-benefit ratios, and three efficient marketing channels at farmer's share.